The role of the 70 kDa subunit of human DNA polymerase alpha in DNA replication. - Collins, K L (1993)
DNA polymerase alpha is the only enzyme in eukaryotic cells capable of starting DNA chains de novo and is required for the initiation of SV40 DNA replication in vitro. We have cloned the 70 kDa subunit of human DNA polymerase alpha (hereafter referred to as the B subunit) and expressed it as a fusion protein in bacteria. The purified fusion protein forms a stable complex with SV40 T antigen, both in solution and when T antigen is bound to the SV40 origin of DNA replication. Analysis of mutant forms of the B subunit indicates that the N-terminal 240 amino acids are sufficient to mediate complex formation. The B subunit fusion protein promotes formation of a complex containing T antigen and the catalytic subunit (subunit A) of DNA polymerase alpha, suggesting that it serves to tether the two proteins. These physical interactions are functionally significant, since the ability of T antigen to stimulate the activity of the catalytic subunit of DNA polymerase alpha is highly dependent upon the B subunit. We suggest that the interactions mediated by the B subunit play an important role in SV40 DNA replication by promoting DNA chain initiation at the origin and/or facilitating the subsequent priming and synthesis of DNA chains on the lagging strand template. The protein may play similar roles in cellular DNA replication.